Storage of volume‐reduced washed platelets in M‐sol additive solution for 7 days. Issue 12 (4th June 2014) - Hirayama, Junichi; Fujihara, Mitsuhiro; Akino, Mitsuaki; Kojima, Shunsuke; Yanagisawa, Ryu; Homma, Chihiro; Kato, Toshiaki; Ikeda, Hisami; Azuma, Hiroshi; Shimodaira, Shigetaka; Takamoto, Shigeru
<x xml:space="preserve">Abstract</x> Background Volume‐reduced washed platelets (VR‐wPLTs), which are prepared by concentrating platelets (PLTs) into a smaller volume of additive solution (AS), may prevent not only circulatory overload, but also adverse reactions caused by plasma components. Although VR‐wPLTs may be quickly degraded due to high PLT concentrations, few studies have examined the effects of storage on VR‐wPLTs. We examined here the in vitro properties of VR‐wPLTs prepared with M‐sol AS during their storage for 7 days. Study Design and Methods Platelet concentrates (PCs) were divided into two equal aliquots (control group and test group). After the centrifugation of both aliquots and removal of as much supernatant as possible, the pellet of the control group was resuspended in 160 mL of M‐sol while that of the test group was resuspended in 80 or 40 mL of M‐sol. The wPLTs of both groups were stored in polyolefin bags with agitation at 20 to 24°C for 7 days. Results The pH values of both groups were maintained at higher than 7.0 during the 7‐day storage. Differences in %disk, CD62P, annexin V, percent hypotonic shock response, and aggregation values between the test group and control group were small for at least 2 days after washing. Conclusions The in vitro properties of VR‐wPLTs were not markedly degraded for at least 2 days. Therefore, the storage properties of PLTs may be maintained in VR‐wPLTs prepared at blood centers until they are administered to patients in hospitals.